2004
DOI: 10.1016/j.actatropica.2004.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Creating spatially defined databases for equitable health service planning in low-income countries: the example of Kenya

Abstract: Equity is an important criterion in evaluating health system performance. Developing a framework for equitable and effective resource allocation for health depends upon knowledge of service providers and their location in relation to the population they should serve. The last available map of health service providers in Kenya was developed in 1959. We have built a health service provider database from a variety of traditional government and opportunistic non-government sources and positioned spatially these fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 18 publications
0
53
1
Order By: Relevance
“…Analyses of national health facilities databases showed that by 2003, this benchmark had been achieved for 82% of the population [25] and that by 2008, a 50% increase in the number of facilities - primarily within the government sector - had brought this estimate up to 89% [26]. In this study, we aimed to characterize spatial variations in child mortality in Kilifi District, Kenya, and evaluate the effect of distance to health facilities on child survival in a context of increased health services density.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of national health facilities databases showed that by 2003, this benchmark had been achieved for 82% of the population [25] and that by 2008, a 50% increase in the number of facilities - primarily within the government sector - had brought this estimate up to 89% [26]. In this study, we aimed to characterize spatial variations in child mortality in Kilifi District, Kenya, and evaluate the effect of distance to health facilities on child survival in a context of increased health services density.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the KEMRI – Wellcome Trust Research Programme (KWTRP), in partnership with the Ministry of Health’s (MoH) Division of Malaria Control, initiated an exercise to geo-code a list of formal health service providers developed from multiple MoH department, NGO and FBO listings [20]. This was the first time a map of health service providers had been developed since 1959 [21].…”
Section: Methodsmentioning
confidence: 99%
“…GIS, combined with participatory methodology, has facilitated the analysis of access to health facilities and disease risk in different populations (Brabyn & Barnett, 2004; Klinkenberg et al, 2004; Martin et al, 2002; Noor, Gikandi, Hay, Muga, & Snow, 2004; Noor, Zurovac, Hay, Ochola, & Snow, 2003; Smith, Barret, & Box, 2000; Zenilman et al, 2002) and in planning for health and social care (Foley, 2002). Hightower et al (1998) show that it is feasible to use Geographical Positioning Systems (GPS) to produce highly accurate maps of communities illustrating altitude of houses, positions of health-care centres and mosquito breeding sites as well as other geographical variables of interest in their longitudinal study of malaria in Kenya.…”
Section: Introductionmentioning
confidence: 99%